2021
DOI: 10.1111/and.14181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead, cadmium, copper and zinc levels on the male reproductive function

Abstract: This study aimed to investigate the effects of heavy metals on measures of male fertility. One hundred and two infertile men with occupational exposure and thirty fertile men were included in this study. Blood and urinary levels of lead, cadmium, zinc and copper were measured by atomic absorption spectrophotometry. Semen parameters and a motile sperm organelle morphology examination were also performed. Measures of hormonal levels, oxidation–reduction potential, DNA fragmentation index and chromatin condensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Therefore, the redox‐modulating function of MLT was investigated. MLT has been proposed to produce both direct and indirect (gene expression‐mediated) antioxidant effects, which could play a key role in preventing the pro‐oxidant effects of Cd and their damaging effect on testicular cells 33,54,55 . Our findings in porcine pre‐pubertal SCs confirm that Cd toxicity is associated with the induction of a pro‐oxidant environment by sustained production and release in the extracellular space of H 2 O 2 (Figure 1).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Therefore, the redox‐modulating function of MLT was investigated. MLT has been proposed to produce both direct and indirect (gene expression‐mediated) antioxidant effects, which could play a key role in preventing the pro‐oxidant effects of Cd and their damaging effect on testicular cells 33,54,55 . Our findings in porcine pre‐pubertal SCs confirm that Cd toxicity is associated with the induction of a pro‐oxidant environment by sustained production and release in the extracellular space of H 2 O 2 (Figure 1).…”
Section: Discussionsupporting
confidence: 73%
“…MLT has been proposed to produce both direct and indirect (gene expression-mediated) antioxidant effects, which could play a key role in preventing the pro-oxidant effects of Cd and their damaging effect on testicular cells. 33,54,55 Our findings in porcine pre-pubertal SCs confirm that Cd toxicity is associated with the induction of a pro-oxidant environment by sustained production and release in the extracellular space of H 2 O 2 (Figure 1). This type of response highlights the phagocyte-like phenotype of these cells and their capability to produce an oxidative burst to protect the testes from exogenous treats.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This helps to maintain the semen quality and homeostasis of testicular environment [ 90 ]. Other studies also confirmed that the zinc concentration in seminal plasma of fertile men is significantly higher than that of infertile men [ 91 ]. Zinc’s antioxidant properties appear to be attributed to its ability to reduce production of hydrogen peroxide and hydroxyl radicals by antagonizing redox-active transition metals (such as iron and copper) [ 92 ].…”
Section: The Application Of Antioxidants In the Treatment Of Male Inf...mentioning
confidence: 63%